Serum asunaprevir concentrations showing correlation with the extent of liver fibrosis as a factor inducing liver injuries in patients with genotype-1b hepatitis C virus receiving daclatasvir plus asunaprevir therapy - Uchida, Yoshihito; Naiki, Kayoko; Kouyama, Jun-ichi; Sugawara, Kayoko; Nakao, Masamitsu; Motoya, Daisuke; Inao, Mie; Nakayama, Nobuaki; Imai, Yukinori; Tomiya, Tomoaki; Mochida, Satoshi (PloS one, 2018)
Liver injury can occur during antiviral therapies with direct-acting antivirals (DAAs), potentially necessitating discontinuation of the therapies, with consequent worsening of the sustained viral response (SVR) rates, in patients with hepatitis C virus (HCV). To clarify the mechanisms involved in serum transaminase level elevation, we performed a retrospective evaluation of the serum concentrations of daclatasvir and asunaprevir, both classified as DAAs, in patients receiving treatment with a combination of the two drugs. Subjects were 278 Japanese patients with genotype-1b HCV who received daclatasvir plus asunaprevir therapy for more than 4 weeks. Serum concentrations of both the DAAs were measured at 4 weeks after the initiation of therapy. Liver injuries including serum AST and/or ALT level elevation to 150 U/L or over were found in 34 patients (12.2%). Multivariate logistic regression analysis identified serum asunaprevir concentrations as being significantly associated with developing liver injury, with an odds ratio of 1.046 (95% confidence interval 1.011-1.082, p<0.05). Serum asunaprevir concentrations showed correlation with the extent of liver fibrosis, estimated by peripheral platelets counts and serum albumin levels and baseline and FIB4 index and serum Mac-2 binding protein glycosylation isomer (M2BPGi) levels at 4 weeks of the therapy; the concentrations were significantly higher among patients showing 3.0 or more of M2BPGi levels than among those with the levels less than 3.0; on the other hand, no such correlation/difference was found in serum daclatasvir concentrations. High serum concentrations of serum asunaprevir, which were associated with the extent of liver fibrosis, appear to provoke the occurrence of liver injury in patients with genotype-1b HCV receiving combined daclatasvir plus asunaprevir therapy.